Envisioning the 2020 Census - National Research Council (U.S.). Panel on the Design of the 2010 Census Program of Evaluations and Experiments; Brown, Lawrence D.; National Research Council (U.S.). Committee on National Statistics (National Academies Press, 2010)
Planning for the 2020 census is already beginning. This book from the National Research Council examines several aspects of census planning, including questionnaire design, address updating, non-response follow-up, coverage follow-up, de-duplication of housing units and residents, editing and imputation procedures, and several other census operations. This book recommends that the Census Bureau overhaul its approach to research and development. The report urges the Bureau to set cost and quality goals for the 2020 and future censuses, improving efficiency by taking advantage of new technologies.